2010
DOI: 10.1007/s00380-010-0065-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of nitroprusside versus nicorandil on the slow/no-reflow phenomenon during coronary interventions for acute myocardial infarction

Abstract: Although slow/no-reflow is a serious problem complicating primary percutaneous coronary interventions (PCI) for acute myocardial infarction (AMI) and is associated with a poor prognosis, its efficacious treatment remains problematic. We compared the acute, in-hospital and long-term (1 year) effects of nitroprusside (NTP) with those of nicorandil (NC) on the slow/no-reflow phenomenon. Forty-nine of 442 consecutive patients with AMI who underwent primary PCI complicated by slow/no-reflow and who received intraco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…That is to say, if one patient's ST2 level exceeded 2.003 ng/mL, we should pay more attention to him/her during PCI or even preventively coronary administration of drugs such as adenosine, nitroprusside or nicorandil before stenting. 29,30 However, in the present study, after collection of peripheral blood samples by venepuncture, it took more than 2 h to obtain the results of sST2 measurement using this Human ST2 ELISA Kit (Medical & Biological Laboratories). As a result, doctors might have missed the optimum PPCI time.…”
Section: Discussionmentioning
confidence: 89%
“…That is to say, if one patient's ST2 level exceeded 2.003 ng/mL, we should pay more attention to him/her during PCI or even preventively coronary administration of drugs such as adenosine, nitroprusside or nicorandil before stenting. 29,30 However, in the present study, after collection of peripheral blood samples by venepuncture, it took more than 2 h to obtain the results of sST2 measurement using this Human ST2 ELISA Kit (Medical & Biological Laboratories). As a result, doctors might have missed the optimum PPCI time.…”
Section: Discussionmentioning
confidence: 89%
“…Possible explanation for the similar final coronary flow status may be the use of adjunctive intracoronary pharmacological treatment and/or additional thrombectomy. Intracoronary administration of nicorandil [9-12], verapamil [11,12] or nitroprusside [13,14] has been shown to preserve coronary flow during PcI. In addition, several studies have shown that thrombectomy is effective in patient with aMI [15,16].…”
Section: Discussionmentioning
confidence: 98%
“…24,25 From the literature, there is greater experience with the usage of SNP as compared to other drugs. A study done by (Kobatake R et al) 26 showed that compared to Nicorandil; SNP was more effective in improving the slow/no-reflow associated with PCI in MI patients and also in the improvement of longterm clinical outcomes. In a cross-over study done on STEMI patients, intracoronary Nicorandil more effectively reduced the index of microvascular resistance dysfunction compared to nitroglycerin after PCI (Ito N et al).…”
Section: Discussionmentioning
confidence: 99%